Relationship of breast fillet deboning time to shear force, pH, cooking loss and color in broilers stunned by high electrical current - Papinaho, Petri A.; Fletcher, Daniel L.; Rita, Hannu J. (Agricultural and Food Science, 1996)
Experiments were conducted to determine the relationships between deboning time and broiler breast meat quality, as determined by objective meat tenderness, pH, color and cooking loss. All birds were processed in a European commercial processing plant using a high current, constant voltage stunning system and air chilling. According to a modified Mitscherlich response equation, pH values reached their ultimate value by 5.77 h post-mortem, with an asymptotic 95 % confidence interval of 5.72 h-5.81 h post-mortem. The shear force data, which were analyzed using a logistic model, suggested that broiler breast fillets should be aged intact on the carcass for 10.58 h, 5.94 h or 2.28 h to guarantee that over 95 % of the fillets reach Allo-Kramer shear forces of 8.0, 9.0 or 11.0 kg/g, respectively. Since acceptable meat tenderness values vary with country, geographical area, or consumer groups, acceptable ranges should be determined according to potential market demands. No relationships between deboning time and fresh meat color or cooking loss was found.